First identification of cryptotephra from the Kamchatka Peninsula in a Greenland ice core: Implications of a widespread marker deposit that links Greenland to the Pacific northwest. (1st February 2018) - Cook, Eliza; Portnyagin, Maxim; Ponomareva, Vera; Bazanova, Lilia; Svensson, Anders; Garbe-Schönberg, Dieter
Abstract: Contiguous sampling of Holocene ice from the NGRIP core, Greenland, has revealed a new rhyolitic cryptotephra that is geochemically identical to the KHG tephra, a widespread marker deposit originating from the Khangar volcano, Kamchatka. This is the first identification of tephra from the Kamchatka Peninsula in Greenland ice and the first finding of the KHG tephra outside Kamchatka. The NGRIP KHG has an age of 7872 ± 50 a BP 1950, and this date will help improve age models for Kamchatka, where existing age estimates of KHG are too young, thus highlighting the importance of locating long-range, low-concentration cryptotephra deposits in well-dated ice cores. In Greenland KHG is located close to the termination of the 8.2 ka BP cooling event that is also a climate feature in palaeo-records of Kamchatka. This tie-point therefore provides a unique opportunity to synchronise records of environmental change in distal locations. Highlights: Widespread Holocene tephra KHG, from Kamchatka, is found as a cryptotephra in the NGRIP ice-core. This is the first identification of tephra from the Kamchatka Peninsula in Greenland ice. NGRIP KHG has an age of 7872 ± 50 a BP and improves age models for Kamchatka. Existing 14 C age estimates for the KHG eruption are too young.